"Secretory" Carcinoma of the Skin Mimicking Secretory Carcinoma of the Breast: Case Report and Literature Review. (September 2016) - Huang, Sixia; Liu, Yan; Su, Jing; Liu, Jianying; Guo, Xiaoning; Mei, Fang; Zheng, Jie; Liao, Songlin
Abstract : Abstract: Secretory carcinoma is a unique kind of adenocarcinoma. It has distinct histological features and a special genetic change, that is, t (12; 15) (p13; q25) translocation which leads to the expression of the ETV6-NTRK3 fusion gene. Secretory carcinoma has been found to occur both in the breast and salivary gland. Here the authors present a case of 22-year-old woman with a unique cutaneous neoplasm located at the axilla. The tumor was characterized histologically with the formation of round to ovoid microcysts and papillary structure, which was similar to the secretory carcinoma of the breast and salivary gland. Furthermore, the gene sequence analysis of reverse-transcription polymerase chain reaction products demonstrated the expression of the ETV6-NTRK3 fusion gene. To the authors' knowledge, this is the first case of secretory carcinoma from the skin which has the same genetic change as those from the breast and salivary gland. Local excision was performed on this patient. She had been followed up for nearly 1 year. No recurrence or metastasis was found yet.